Vitis vinifera (Vine Grape) as a Valuable Cosmetic Raw Material - Marta Sharafan; Magdalena A. Malinowska; Halina Ekiert; Beata Kwaśniak; Elżbieta Sikora; Agnieszka Szopa (Pharmaceutics, 2023)
This review refers to botanical, ecological and phytochemical characteristics of Vitis vinifera L. (vine grape)–a species, the valuable properties of which are widely exploited in the food industry and in recent times in medicine as well as in phytocosmetology. The general characteristic of V. vinifera, followed by the chemical composition and biological activities of different extracts obtained from the plant (fruit, skin, pomace, seed, leaf and stem extracts), are provided. A concise review of the extraction conditions of grape metabolites and the methods of their analysis are also presented. The biological activity of V. vinifera is determined by the presence of high contents of polyphenols, mainly flavonoids (e.g., quercetin, kaempferol), catechin derivatives, anthocyanins and stilbenoids (e.g., trans-resveratrol, trans-ε-viniferin). The review pays particular attention to the application of V. vinifera in cosmetology. It has been proven that V. vinifera possesses strong cosmetological-related properties, such as anti-ageing properties, anti-inflammatory properties and skin-whitening properties. Moreover, a review of studies on V. vinifera biological activities, which are of particular interest for dermatologic problems, are disclosed. Furthermore, the work also emphasises the importance of biotechnological studies on V. vinifera. The last part of the review is addressed to the safety of the use of V. vinifera.